2018
DOI: 10.3390/ma11122451
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition and Thermal Reaction Process of PTFE/Al/MnO2 Fluorinated Thermite

Abstract: To better understand the thermal decomposition and reaction process of a fluorine-containing powdery thermite, PTFE/Al/MnO2, reactions at different temperatures were investigated by the TG/DSC-MS technique. The corresponding reaction products were characterized with XRD phase analysis. Another three thermite materials, i.e., PTFE/Al, Al/MnO2, and PTFE/MnO2, were also prepared for comparison. Results showed that PTFE behaved as both oxidizer and reducer in PTFE/Al/MnO2 fluorinated thermite. The thermal decompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…So peak A is the melting endothermic peak of PTFE. Starting from 509 °C, the TG curve shows a sharp drop in sample mass and the loss is 100%, and peak B starts at 514.02 °C, indicating that peak B is the endothermic decomposition peak of PTFE, and the decomposition product is gaseous product C 2 F 4 with the boiling point of −76 °C [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So peak A is the melting endothermic peak of PTFE. Starting from 509 °C, the TG curve shows a sharp drop in sample mass and the loss is 100%, and peak B starts at 514.02 °C, indicating that peak B is the endothermic decomposition peak of PTFE, and the decomposition product is gaseous product C 2 F 4 with the boiling point of −76 °C [24].…”
Section: Resultsmentioning
confidence: 99%
“…The boiling point of the produced AlF 3 is low and could not hinder the reaction by covering on the surface of Al particles [27]. The peak temperature of peak D is 659 °C, resulting from heat absorption of Al powder, which has not reacted completely at about 660 °C [24].…”
Section: Resultsmentioning
confidence: 99%
“…Because type B specimen possessed excellent ductility and absorbed the most energy during compression, the energy could stimulate the thermite reaction as well as the reaction of Al and PTFE. Zhang et al 27 investigated the thermal decomposition and thermal reaction process of PTFE/Al/MnO 2 uorinated thermite. Experimental results indicate that PTFE behaved as both oxidizer and reducer in PTFE/Al/MnO 2 uorinated thermite.…”
Section: Reaction Phenomenon Under Quasi-static Compressionmentioning
confidence: 99%
“…In the last ten years, the main research based on Al/PTFE reaction materials is as follows: (1) study on the composition ratio and mixing methods of Al/PTFE-based active materials; (2) study on the mechanical properties, reaction characteristics, impact sensitivity, ignition mechanism and hot spot formation mechanism of crack tip of Al/PTFE-based active materials; (3) study on the energy release characteristics of Al/PTFE-based active materials; (4) study on the establishment of a theoretical model of impact-induced chemical reaction of Al/PTFE-based active materials. Among them, some scholars introduce high density metals such as Ni [ 13 ], W [ 14 , 15 ] and Ta [ 16 ] into Al/PTFE-based active materials to improve their hardness, density, strength and other characteristics; some scholars have added metal oxides CuO [ 17 ], Fe 2 O 3 [ 18 ] and MnO 2 [ 19 ] to Al/PTFE-based active materials to improve their reaction characteristics; some scholars have added high-energy additives such as TiH 2 [ 20 ] and ZrH 2 [ 21 ] to Al/PTFE-based active materials to improve their energy release characteristics. Based on published literature of the above studies, it can be found that most scholars mainly study the influence of distribution ratio, particle size and other factors on material properties through a given sintering control curve, while few scholars study the influence of sintering control factors on material properties.…”
Section: Introductionmentioning
confidence: 99%